Measuring pandemic home-work conditions to determine ergonomic recommendation relevance. - Black, Nancy L.; St-Onge, Samuelle; Davis, Kermit; Kotowski, Susan (Work, 2022)
BACKGROUND: Computer-intensive office work associations with health challenges may intensify following COVID-19 pandemic-related changes to home-based office work. OBJECTIVE: To determine working conditions, perception and physical elements affecting health after pivoting to full time home-work. METHODS: An online questionnaire addressed physical, productivity, motivation, and work-practice factors. Photos of the worker in their home-work environment showed side and front-back perspectives. RESULTS: Sixteen questionnaires were received, and 12 respondents supplied photos. Home and office workplace differences varied. Ten felt productivity was affected, most often positively. Four noted increased pain or fatigue intensity, particularly in the eyes, neck / head, lower back, and shoulders. Working posture was not optimal; six didn't use traditional chair-sitting for up to half the day. Forward and backward trunk inclination accounted for at least 10% of the workday for 12 respondents; lateral inclination affected ten and eight had unsupported legs. Fifteen used an adjustable chair, but photos revealed ergonomic recommendations were not consistently followed. Fourteen participants communicated regularly by telephone, eight only for moderate duration and ten using adapted telephone equipment. Half of the ROSA scores were high. CONCLUSIONS: Workers forced into telework during the pandemic experience positive and negative impacts. Postures vary more than in offices, potentially increasing health risk.